Perancangan Struktur Gedung Perkuliahan 4 Lantai Dengan Metode Sistem Rangka Pemikul Momen Menengah (SRPMM) di Wilayah Sukoharjo - Alma, Al Janatul; , Budi Setiawan, S.T.,M.T (2016)
The increasing number of Universitas Muhammadiyah Surakarta's students needs to be balanced with the good amenities, facilities and infrastructures to support learning activities. The purpose of this final project is to design the structure of 4 floors lecture building using Intermediate Moment Resisting Frame (IMRF) methode in Sukoharjo. The design of this lecture building structure refers to the latest Indonesia's standart regulation (SNI) published by National Standardization Agency (BSN), which are SNI 2847: 2013, SNI 1726: 2012 and SNI 1727: 2013. This lecture building design includes the structure of roof plate, floor plates, stairs, columns, beams, pile foundation, poer and sloof. The building is located in Pabelan (coordinates: -7.5595; 110.7644), thus the value of SS = 0.749, S1 = 0.314 and N ̅ = 43,75 includes in SD category (intermediate soil), earthquake resistant building with response modification factor (R) = 5, primary building factor (Ie) = 1.5. The concrete quality that is used are f'c = 25 MPa, steel quality fy = 350 MPa (fy,slab = 240 MPa), fyt = 240 MPa. Based on the design, we got 100 mm for the roof slab thickness and 120 mm for floor slabs thickness, beam and sloof dimensions is 300/500 mm, 1st floor columns use 500x500 mm of dimensions, and 2nd floor up to 4th floor columns use 400x400 mm of dimensions. 18000 mm deep piles uses 300x300 mm of dimensions by using poer with 1750x1750x650 mm dimensions.